Habeas Mentem and Neurotechnology: A Brief Introduction to the Ethical Problem of Neurorights Protection - Bicocchi, Julie (Organisms. Journal of Biological Sciences, 2022)
Over the last twenty years neuroscience has evolved much more rapidly than the ability to update national and international human rights law. In this regulatory vacuum new and potentially dangerous market niches have been created for more and less invasive devices dedicated to our mental activities. How, and in which contexts, it is still possible to fill this serious gap is a topic that the scientific community and civil society must discuss as soon as possible. Otherwise, dystopian scenarios might open up, in which algocracy and technocracy could converge into a regime of perpetual overpowering of our humanity.